Childhood trauma experiences and dark triad traits in women: the mediating role of social support - Abdollahi, Masoome; Saadati, Nadereh; Rahsepar Monfared, Farnaz (Psychology of Woman Journal, 2021)
The current research aimed to determine the role of childhood trauma experiences with dark triad traits with the mediation of social support. The statistical population was women referred to Tehran counseling centers in the period of 2020-2021. After conducting the initial interview, 250 eligible women were selected purposefully and responded to the questionnaires about childhood injuries, dark personality traits, and perceived social support. The collected data were analyzed using correlation coefficients and structural equations. The correlation coefficients showed a negative correlation between social support with the total score of dark triad traits and the components of narcissism, Machiavellianism, and antisociality. There is a negative correlation between emotional abuse, physical abuse, sexual abuse, emotional neglect, and physical neglect with the total score of dark triad traits and the components of narcissism, Machiavellianism, and antisociality. Also, with perceived support and the components of perceived support from the family, perceived support from important people, and perceived support from others, there is a negative correlation at a significant α=0.01 level. The path coefficients model results showed a significant direct relationship between the components of childhood trauma (emotional abuse, physical abuse, sexual abuse, emotional neglect, and physical neglect) with dark triad traits and social support. Also, there is a significant negative direct relationship between social support and dark triad traits. The experiences of childhood traumas are influenced by the vulnerability of the personality and the long-term experiences of the growth period, and these factors add to the complexity of personality traits over time.